Treatment of radial artery graft spasm after coronary artery bypass grafting - Valaika, Arunas; Kalinauskas, Gintaras; Ivaskeviciene, Loreta; Samalavicius, Robertas; Butkuviene, Irena; Norkunas, Gediminas; Uzdavinys, Giedrius (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Spasm of radial artery (RA) used as a conduit for CABG (coronary artery bypass graft) surgery is a rare phenomenon. Our experience with surgical treatment of RA spasm is reported. The patient with triple vessels disease was scheduled for elective CABG surgery. Both radial and mammary arteries were used to create four distal anastomoses. Seven hours after the patient was admitted to intensive care unit his condition started to deteriorate, severe ischemia and low cardiac output syndrome developed. Resternotomy was performed and intraortic balloon was inserted through the ascending aorta (patient had severe peripheral artery disease). During reexploration both RA‘s conduits were found spastic. Nitroglycerin and papaverin solutions were injected into the adjacent tissues of radial arteries. Following this treatment RA became dilated, ST segment on ECG came to normal. RA spasm can occur in rare cases despite prophylactic antispastic measures. However, early diagnosis and initiation of appropriate treatment might have an impact on outcome in this life-threatening situation.